PHD2 inactivation in Type I cells drives HIF‐2α‐dependent multilineage hyperplasia and the formation of paraganglioma‐like carotid bodies. (19th August 2018) - Fielding, James W.; Hodson, Emma J.; Cheng, Xiaotong; Ferguson, David J. P.; Eckardt, Luise; Adam, Julie; Lip, Philomena; Maton‐Howarth, Matthew; Ratnayaka, Indrika; Pugh, Christopher W.; Buckler, Keith J.; Ratcliffe, Peter J.; et al.
Abstract : Key points: The carotid body is a peripheral arterial chemoreceptor that regulates ventilation in response to both acute and sustained hypoxia. Type I cells in this organ respond to low oxygen both acutely by depolarization and dense core vesicle secretion and, over the longer term, via cellular proliferation and enhanced ventilatory responses. Using lineage analysis, the present study shows that the Type I cell lineage itself proliferates and expands in response to sustained hypoxia. Inactivation of HIF‐2α in Type I cells impairs the ventilatory, proliferative and cell intrinsic (dense core vesicle) responses to hypoxia. Inactivation of PHD2 in Type I cells induces multilineage hyperplasia and ultrastructural changes in dense core vesicles to form paraganglioma‐like carotid bodies. These changes, similar to those observed in hypoxia, are dependent on HIF‐2α. Taken together, these findings demonstrate a key role for the PHD2–HIF‐2α couple in Type I cells with respect to the oxygen sensing functions of the carotid body. Abstract: The carotid body is a peripheral chemoreceptor that plays a central role in mammalian oxygen homeostasis. In response to sustained hypoxia, it manifests a rapid cellular proliferation and an associated increase in responsiveness to hypoxia. Understanding the cellular and molecular mechanisms underlying these processes is of interest both to specialized chemoreceptive functions of that organ and, potentially, to the general physiology and pathophysiology of cellular hypoxia. We have combined cell lineage tracing technology and conditionally inactivated alleles in recombinant mice to examine the role of components of the HIF hydroxylase pathway in specific cell types within the carotid body. We show that exposure to sustained hypoxia (10% oxygen) drives rapid expansion of the Type I, tyrosine hydroxylase expressing cell lineage, with little transdifferentiation to (or from) that lineage. Inactivation of a specific HIF isoform, HIF‐2α, in the Type I cells was associated with a greatly reduced proliferation of Type I cells and hypoxic ventilatory responses, with ultrastructural evidence of an abnormality in the action of hypoxia on dense core secretory vesicles. We also show that inactivation of the principal HIF prolyl hydroxylase PHD2 within the Type I cell lineage is sufficient to cause multilineage expansion of the carotid body, with characteristics resembling paragangliomas. These morphological changes were dependent on the integrity of HIF‐2α. These findings implicate specific components of the HIF hydroxylase pathway (PHD2 and HIF‐2α) within Type I cells of the carotid body with respect to the oxygen sensing and adaptive functions of that organ. Key points: The carotid body is a peripheral arterial chemoreceptor that regulates ventilation in response to both acute and sustained hypoxia. Type I cells in this organ respond to low oxygen both acutely by depolarization and dense core vesicle secretion and, over the longer term, via cellular proliferation and enhanced ventilatory responses. Using lineage analysis, the present study shows that the Type I cell lineage itself proliferates and expands in response to sustained hypoxia. Inactivation of HIF‐2α in Type I cells impairs the ventilatory, proliferative and cell intrinsic (dense core vesicle) responses to hypoxia. Inactivation of PHD2 in Type I cells induces multilineage hyperplasia and ultrastructural changes in dense core vesicles to form paraganglioma‐like carotid bodies. These changes, similar to those observed in hypoxia, are dependent on HIF‐2α. Taken together, these findings demonstrate a key role for the PHD2–HIF‐2α couple in Type I cells with respect to the oxygen sensing functions of the carotid body.